tan² A cos² A = 1 – cos²A.
Answers
Answered by
2
STEP BY STEP EXPLANATION GIVEN IN THE ABOVE PIC
Attachments:
![](https://hi-static.z-dn.net/files/dd8/933dd00345f2b80bcf67cc6b437ec045.jpg)
Answered by
0
Answer:
Let me prove the question in a reverse manner
RHS (Right Hand Side)
=1 - cos^2A
=sin^2A+cos^2A-cos^A ( sin^2+cos^2=1)
=sin^2A
Now you multiply with cos^2A/ cos^2A
=sin^2A × cos^2A/cos^2A
=sin^2A/cos^2A×cos^2A
(tan^2A=sin^2A/cos^2A)
=tan^2A×cos^2A
= LHS
Similar questions
English,
6 months ago
India Languages,
6 months ago
Social Sciences,
1 year ago
Chemistry,
1 year ago
English,
1 year ago
Math,
1 year ago
Math,
1 year ago